Electronic circuit design and simulation for silicon on-chip photodetectors - Chua, Angela Xin Yi (Nanyang Technological University, 2022)
In many optical distance measuring applications where great accuracy is required, transimpedance amplifiers (TIA) are commonly utilized for front-end signal conditioning. A TIA is a sensitive and fast current measurement device that converts a generally weak input current signal to a significant output voltage. The project focuses on the research on transimpedance amplifier applications and performances using hardware and software.